HUBUNGAN TINGKAT PENGETAHUAN DAN SUMBER INFORMASI ORANG TUA DENGAN PEMBERIAN VAKSIN HPV PADA SISWI KELAS V DI SDN MERUYA UTARA 02 DAN SDN SRENGSENG 03 TAHUN 2022 - Dinah Hanifah (2022)
Jakarta, one of the demonstration cities for the HPV vaccination program, has a low coverage compared to the other two cities, Surabaya and Yogyakarta. Based on the assessment results Jakarta, as one of the demonstration cities of the HPV vaccination program, has a low coverage compared to Surabaya and Yogyakarta. Based on the assessment results after introducing the HPV vaccination program in Indonesia in 2017, the coverage of HPV vaccination in Jakarta for dose 1 was 92%. In 2018 the coverage of HPV in Jakarta decreased to 89.4%. In 2021, based on data from the West Jakarta Health Sub-Department, the target for fifth-grade elementary school students in the Kembangan sub-district has the lowest single-dose vaccination coverage of 86.2%. This study aims to analyze the relationship between the level of knowledge and sources of parental information with the provision of HPV vaccine to fifth-grade students at SDN Meruya Utara 02 and SDN Srengseng 03. This study was quantitative with a cross-sectional design, using a total sampling technique with a sample size of 87 parents. Data analysis used the chi-square test. The results showed the p-value = 0.000 for the knowledge level variable and the p-value = 0.002 for the information source variable. This study concludes that there is a significant relationship between the level of knowledge and sources of parental information with the administration of the HPV vaccine. Health workers and schools are expected to hold socialization and education for parents before implementing the HPV vaccine to increase parental participation. Keywords: HPV Vaccine, Knowledge, Parents, Source of Information.